Objawienie w teologii patrystycznej - Rusecki, Marian (Vox Patrum, 2008)
The issue of his article is the reflection of the Divine Revelation that had been started from the beginning of Patristic. The earliest Christians documents and the first Fathers of the Church both expressed the Revelation by words like: mystery, salvation, pedagogics. The Revelation comes from the Divine economy and ex- presses in history, what happens step by step. The Fathers of the Church started to expose the unity of the Divine economy. It showed the unity of the Divine Revelation and his constantly progress. The Fathers of the Church started to point to the arguments of credibility of Christianity like the argument from prophetic, but not only. Some of the factors had influenced to the meaning of Revelation. There were for example: Jewish and heretics.